The metaphysics of German idealism a new interpretation of Schelling's "Philosophical investigations into the essence of human freedom and the matters connected therewith" (1809) - Heidegger, Martin 1889-1976 (Polity, 2021)
Zusammenfassung: "A major work by one of the most influential philosophers of the 20th century, published here in English for the first time"--
Keywords: Schelling, Friedrich Wilhelm Joseph von -- 1775-1854 -- Philosophische Untersuchungen über das Wesen der menschlichen Freiheit und die damit zusammenhängenden Gegenstände; Schelling, Friedrich Wilhelm Joseph von -- 1775-1854; Schelling, Friedrich Wilhelm Joseph von 1775-1854; Schelling, Friedrich Wilhelm Joseph von 1775-1854--Philosophische Untersuchungen über das Wesen der menschlichen Freiheit; Idealism, German; Metaphysik